Anti-atherosclerosis mechanisms associated with regulation of non-coding RNAs by active monomers of traditional Chinese medicine - Liu, Guoqing; Tan, Liqiang; Zhao, Xiaona; Wang, Minghui; Zhang, Zejin; Zhang, Jing; Gao, Honggang; Liu, Meifang; Qin, Wei (Frontiers in Pharmacology, 2023)
Atherosclerosis is the leading cause of numerous cardiovascular diseases with a high mortality rate. Non-coding RNAs (ncRNAs), RNA molecules that do not encode proteins in human genome transcripts, are known to play crucial roles in various physiological and pathological processes. Recently, researches on the regulation of atherosclerosis by ncRNAs, mainly including microRNAs, long non-coding RNAs, and circular RNAs, have gradually become a hot topic. Traditional Chinese medicine has been proved to be effective in treating cardiovascular diseases in China for a long time, and its active monomers have been found to target a variety of atherosclerosis-related ncRNAs. These active monomers of traditional Chinese medicine hold great potential as drugs for the treatment of atherosclerosis. Here, we summarized current advancement of the molecular pathways by which ncRNAs regulates atherosclerosis and mainly highlighted the mechanisms of traditional Chinese medicine monomers in regulating atherosclerosis through targeting ncRNAs.